ICSH recommendations for assessing automated high‐performance liquid chromatography and capillary electrophoresis equipment for the quantitation of HbA2. (15th September 2015) - Stephens, A. D.; Colah, R.; Fucharoen, S.; Hoyer, J.; Keren, D.; McFarlane, A.; Perrett, D.; Wild, B. J.; ,
Summary: Automated high performance liquid chromatography and Capillary electrophoresis are used to quantitate the proportion of Hemoglobin A2 (HbA2 ) in blood samples order to enable screening and diagnosis of carriers of β‐thalassemia. Since there is only a very small difference in HbA2 levels between people who are carriers and people who are not carriers such analyses need to be both precise and accurate. This paper examines the different parameters of such equipment and discusses how they should be assessed.